Vibration based characterization of tool wearing in micro-milling of ceramics. (December 2021) - Móricz, László; Viharos, Zsolt János
Abstract: The main aim of the paper is to monitor the micro-milling tool wearing process offline, by a microscopic tool measurement on one hand, and using high-frequency vibration measurement online, during the cutting process, on the other. Relations between the rake face wear stages and the measured online and offline parameters were determined applying an own-developed, artificial neural network based feature selection solution. As the main result, the experiment-based research appoints that measured vibration variable component(s) which characterizes the key, three tool wearing phases in the same way as the real rake face wearing stages occur.